Voicing out or switching away? A psychological climate perspective on customers' intentional responses to service failure. (February 2020) - Li, Chang-Jun; Li, Fuli; Fan, Pan; Chen, Kai
Highlights: Psychological climate for communication safety enhances complaint intentions. Harmony enhancement promotes psychological climate for communication safety. Customer's intentions predict subsequent behavioral responses to service failure. Personality trait, psychological climate, and intentions shape customer behaviors. Abstract: This research explores why customers who experience service failure are willing to complain directly to service providers but unlikely to switch to other service providers. We bring in the concept of psychological climate for communication safety (PCCS) to the service failure context and explore how customers' perception of the social environment as open and supportive for communication affects their complaint and service switching intentions and behaviors. We further identify customer harmony enhancement as an important personality trait predictor of PCCS. Based on two field studies and one scenario-based experimental study, our findings consistently show that PCCS mediates the positive effect of customer harmony enhancement on customer complaint intentions. Customer harmony enhancement exerts a positive indirect effect on customer complaint behavior serially through PCCS and customer complaint intentions. However, our findings relating to customer service switching intentions are inconsistent across the three studies. Theoretical and practical implications are discussed.